HOMELESSNESS IN MALAYSIA: VICTIMS OF CIRCUMSTANCE OR BY CHOICE? - Ghee, Wee Yu; Omar, Raja Norliana Binti Raja (ASIAN JOURNAL FOR POVERTY STUDIES (AJPS), 2015)
This paper discusses the issues of homelessness in Malaysia, what constitutes and causes homelessness in MalaysiaÂ and how the society and government can help this marginalised group, according to public opinion. There is no officialstatistics showing the number of homeless in the city as only a few non-governmental organisations (NGOs) are awareÂ of their existence. Needless to mention, the reasons why they end up sleeping on the streets. Homelessness affectsÂ thousands across Malaysia â people from all ethnicities, age groups, education levels, and geographic regions.Â Despite the pervasiveness of homelessness, people who are homeless are typically blamed for their homelessness. TheÂ media and public perpetuate myths of homeless women and men as "lazy", unmotivated people prone to making poorÂ choices or as deviants who care nothing of the society or "being a burden". Observations, interviews and discussionsÂ were conducted among urban citizens. Data collected include their opinions, awareness and perceptions on the homelessin the country and various assistance currently available. Findings show not many are aware of the state of theÂ homeless in the country. However, majority are concerned and willing to help through donations, food distribution,and creations of job and social services programs organized by the government or NGOs.